Entrepreneurial Intentions: Between Entrepreneurial Knowledge, Entrepreneurial Skills and Perceived Control Behavior - Kurjono Kurjono (Dinamika Pendidikan, 2022)
This study aims to analyze the effect of entrepreneurial knowledge, entrepreneurial skills, and planned control behavior on entrepreneurial intentions. The grand theory used is Teri Planned Behavior from Ajzen (1991). The explanatory survey method was employed as the research method of the study. The research population comprised 506 students with a sample size of 218 respondents. The research sample was taken from a population of all Indonesian accounting education students consisting of students who had attended entrepreneurship courses from the Universitas Pendidikan Indonesian (UPI), Universitas Negeri Yogyakarta Negeri (UNY), Universitas Sebelas Maret (UNS), Universitas Negeri Surabaya (UNESA), Universitas Negeri Malang (UM), Universitas Negeri Makasar (UNM) and Universitas Negeri Medan (UNIMED). As the strategy to collect data, all questionnaires in this study have been tested for validity and reliability. Data were analyzed through descriptive analysis and path analysis. The results indicate that entrepreneurial knowledge did not affect perceived control behavior. Thus, variable trimming is conducted. Entrepreneurial skills have a positive effect on perceived control behavior. Similarly, entrepreneurial skills impact entrepreneurial intentions. Perceived behavior control has a positive effect on entrepreneurial intentions. Perceived behavior control is the most dominant variable in influencing entrepreneurial intentions. Future research is recommended to increase entrepreneurship from indicators of experience such as knowing client's problems and entrepreneurial skills, for example, indicators of recognizing opportunities, perceived behavior control through indicators of having opportunities for success, and entrepreneurial intentions through the business ability to start a business.